2014
DOI: 10.1016/j.joa.2014.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Remote monitoring of cardiovascular implantable electronic devices in Japan

Abstract: The number of patients with chronically implanted cardiovascular implantable electronic devices (CIEDs) keeps growing, and device clinics of major hospitals may soon be unable to fully accommodate the increasing amount of follow‐up activities. Consequently, the remote monitoring (RM) technology introduced in Japan in 2010 has been rapidly gaining widespread application in the management of CIEDs. A modern remote monitor not only acts as an alternative to a device clinic, but also as a security monitor for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…The number of patients with chronically implanted cardiovascular implantable electronic devices (CIEDs) is continuously increasing, and device clinics at hospitals may soon be unable to fully cope with the increasing number of follow-up activities [1]. Current guidelines necessitate one or two follow-up assessments per year for patients implanted with a pacemaker (PM) [2].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The number of patients with chronically implanted cardiovascular implantable electronic devices (CIEDs) is continuously increasing, and device clinics at hospitals may soon be unable to fully cope with the increasing number of follow-up activities [1]. Current guidelines necessitate one or two follow-up assessments per year for patients implanted with a pacemaker (PM) [2].…”
Section: Introductionmentioning
confidence: 99%
“…The objective of disease management is to reduce operating costs without lowering effectiveness by creating disease-specific pathways of diagnosis and care in patients at a high risk of heart failure, thus allowing doctors to quickly detect and respond to adverse events, which may also improve patients’ health status [1,8]. Previous studies have reported that although telemedicine requires an initial financial investment, such interventions eventually result in a substantial reduction in the medical costs over a long period of time [9].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation